Academic writing in social work education: reflections from an international classroom. Issue 1 (2nd January 2017) - Christensen, Jonas; Hjortsjö, Maria; Wärnsby, Anna
Abstract: The affordances of processing subject knowledge through academic writing are rarely explicitly realised in social work education. In this article, we highlight the link between instructors' efforts to facilitate students' academic writing and students' perceived increase of knowledge in the subject of social work in an international context. Based on instructors' and students' reflections collected before, during, and after a course, we aimed to answer the following questions: in what way can academic writing support students' learning in social work? What are students' reflections on the pedagogical model involving academic writing? The theoretical framework for the analysis was based on learning theories focusing on collaborative learning. The main conclusion is that the instructors' awareness of how to scaffold students' ability to write in an academic context and to develop the students' understanding of social work in a local and global context is an important factor in student learning.